Just Beyond: The Scare School - Vol 1 - Stine, R. L.; Matthews, Nichole; Matthews, Kelly (Comic book artist); ABDO Publishing Company (Minneapolis, Minnesota : Spotlight, a division of ABDO, 2021)
Surviving middle school is hard enough, but when Jess, Josh, and Marco encounter a strange and deadly creature wandering the halls of The Scare School, it leads them to a sinister secret in the boiler room. As they leave their school behind, these three unsuspecting students enter a horrifying reality just beyond the one they know, one filled with supernatural terror and fright. Will they survive the harrowing journey and save the other children they find trapped there, or will they forever be trapped on the wrong side of The Scare School?
Keywords: Students -- Comic books, strips, etc; Middle school students -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Students -- Fiction; Middle school students -- Fiction; Middle schools -- Fiction; Cartoons and comics; Horror comics; Graphic novels; Comics (Graphic works)